Analisis Kebutuhan Pengembangan Bahan Ajar Kimia Berbasis Elektronik Terintegrasi Model Pembelajaran Problem Based Learning Pada Siswa SMA Kelas X Kota Medan - Asmi, Andalia; Silaban, Saronom; Silaban, Ramlan (Efektor, 2024)
This study aims to fulfill the requirement for improving chemistry instruction materials for SMA classes, and the study's findings will be consulted for further information in the development of electronic chemistry teaching materials. A qualitative descriptive method was employed in the study. Four secondary schools participated in this study in Medan City by interviewing four teachers from each school and observing the IPA-X class with 80 students. It has been done. As the Study shows, teachers still use traditional teaching methods and only use school-published textbooks. The teaching materials must be revised, as students still use electronic media in 48.9% of the survey results. I found that they made use of the training materials provided. The required percentage is 53.6%. These results demonstrate the need to develop electronic materials that help students comprehend the subject matter and facilitate learning and exploring the learning process.